A Process Semantics for BPMN - Wong, P; Gibbons, J (Kitakyushu‚ Japan, 2008)
Business Process Modelling Notation (BPMN), developed by the Business Process Management Initiative (BPMI), intends to bridge the gap between business process design and implementation. However, the specification of the notation does not include a formal semantics. This paper shows how a subset of the BPMN can be given a process semantics in Communicating Sequential Processes. Such a semantics allows developers to formally analyse and compare BPMN diagrams. A realistic example of a complex business process is included.